Analysis of the Influence of Msme’s Taxpayer Compliance: Understanding of Taxation, Tax Rates, and Tax Sanctions - Fatihatunnisa, Tri Ajeng; Muhaimin, Faizal; Janiman (Indonesian Journal of Advanced Research, 2024)
This research aimed to test the factors that impact MSME tax compliance in Cirebon City. The population of this research consisted of all MSMEs in the city of Cirebon. The Slovin formula was used to determine the sample size, and the outcome was 100 responders. In this research, a questionnaire was used as the data gathering tool. This research uses SPSS 26 in data processing. Multiple linear regression tests were used in quantitative approaches of data analysis. The test results of each variable show numbers below 0.05 which means that there is an influence of each variable. The results demonstrated that taxpayer compliance (Y) was positively impacted by the variables of tax comprehension (X1), tax rates (X2), and tax sanctions (X3). This research can be one of the considerations for the government regarding MSME tax regulations that have not been maximized in realization. The obstacles related to distributing questionnaires to respondents cause limitations related to the limits or criteria that determine the scope of the research.